An investigation on laser welding parameters on the strength of TRIP steel - Rahul, Khot S. (Strojniški vestnik, 2021)
The energy required for joining steel segments by using laser welding is relatively very low compared with arc welding, gas welding, or any other conventional welding techniques. Moreover, the rapid cooling may create a significant effect on different regions, such as the fusion zone (FZ), heat affected zone (HAZ), and base metal (BM), and in turn affect different parameters. In this study, the characteristics of the laser-welded joint were investigated by varying laser power, welding velocity and incident angle, and tensile strength. In our, experiments. the microhardness was increased by varying the power of laser welding. The strength of the joint was increased to 549 MPa with 2200 W high power, 30 mm/s velocity, and 80% laser incident angle. By increasing the power and velocity of the laser, the welding gun strength was improved; conversely, the angle of laser incident on the welding location decreased while its strength was increased.
Keywords: jeklo TRIP; laser Nd:YAG; laser welding; lasersko varjenje; mechanical strength; mehanska trdnost; microhardness; mikrotrdota; Nd:YAG laser; termovizijska kamera; TRIP steel